Comparative Study of Outcomes between Pollicization and Microsurgical Second Toe-Metatarsal Bone Transfer for Congenital Radial Deficiency with Hypoplastic Thumb - Tan, Jacqueline Siau Woon; Tu, Yuan-Kun (Journal of Reconstructive Microsurgery, 2013)
With the advent of microsurgery, various surgical options exist to treat the hypoplastic thumb in patients with radial deficiency. This study aims to compare the outcome assessments between index finger pollicization and microsurgical second toe-metatarsal bone transfers for thumb reconstruction in these patients. Between 1996 and 2002, a total of 30 patients were included and equally divided into two groups: Group 1 (pollicization) and Group 2 (toe transfer). The mean patient age was 3.2 years, and the mean duration of follow-up was 8 years. The average operation time was 2.6 hours and 8.0 hours for Group 1 and Group 2, respectively. The success rate of thumb reconstruction was 100% in both groups. All the children achieved both small and large grip functions as well as complete sensory recovery. Patients who underwent pollicization had earlier motor and sensory recovery and better range of motion; whereas, patients who received toe transfers had higher parental satisfaction and performed better in some activities of daily living.
Keywords: hypoplasia; pollicization; radial deficiency; toe-metatarsal bone transfer